Analisis Business Model Canvas (BMC) pada Usaha Undangan Digital Untukmu - Andisa, Gany; Al Hapid, Nabil Malik; Kuntari, Wien (Populer: Jurnal Penelitian Mahasiswa, 2024)
The development of digital technology has brought significant changes in the invitation industry, replacing conventional paper invitations with digital invitations that are more environmentally friendly and efficient. This study aims to analyze the business model of the Untukmu digital invitation business using the Business Model Canvas (BMC) framework. BMC includes nine key elements, namely customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structures. The results of the analysis show that the personalization approach, interactive features such as RSVP and photo galleries, and digital promotion strategies through social media are the main competitive advantages of this business. This study also identifies the challenges faced, such as market competition and limitations of UI design, and provides strategic recommendations to overcome these obstacles. With this analysis, it is hoped that the Untukmu digital invitation business can increase its competitiveness and business sustainability.